The Effect of Beading Activities on the Fine Motor Skills of Children Aged 4–5 Years at TK Labschool Unesa 1 - Laili, Fatma Nur; Hasibuan, Rachma; Dewi, Dwi Jayanti Kurnia; Komalasari, Dewi (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to determine the effect of beading activities on the fine motor skills of children aged 4–5 years at TK Labschool Unesa 1. The background of this research problem is the lack of stimulation in fine motor activities, causing children to experience difficulties in pinching small objects, controlling finger movements, and performing activities requiring hand–eye coordination. This study employed a quantitative approach with a one-group pretest–posttest design. The subjects were 31 children from Group A. Data were collected through observation using an assessment sheet covering children’s flexibility, finger strength, and accuracy, and analyzed using the paired sample t-test. The results showed a significant difference between the pretest and posttest scores after the children participated in beading activities. The average score before treatment (pretest) was 44%, and after treatment (posttest) was 71%, with a score difference of 27%, indicating the influence of beading activities. This influence was evident from improvements in children’s ability to pinch, insert beads, and coordinate their hands and eyes after participating in beading activities. This occurred because the researcher provided three treatments and followed beading stages appropriate to the children’s developmental age.